2010
DOI: 10.1007/s10552-010-9515-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and risk of incident cancer: a large population-based cohort study in Israel

Abstract: Type 2 diabetes mellitus has been associated with an increased risk of a variety of cancers in observational studies, but few have reported the relationship between diabetes and cancer risk in men and women separately. The main goal of this retrospective cohort study was to evaluate the sex-specific risk of incident overall and site-specific cancer among people with DM compared with those without, who had no reported history of cancer at the start of the follow-up in January 2000. During an average of 8 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 62 publications
(67 reference statements)
3
121
0
3
Order By: Relevance
“…There was also no significant difference overall in cancer deaths between the groups assigned to more intensive vs less intensive glucose lowering. The overall cancer event rate observed in our study of patients with long standing type 2 diabetes (1.33 per 100 PY) was similar to that of one large population-based study of people with diabetes (1.31 per 100 PY) [23] and [24]. Notably, both these cohort studies also examined cancer incidence in individuals free of diabetes and reported lower overall event rates (1.19 and 0.77 per 100 PY, respectively).…”
Section: Discussionsupporting
confidence: 87%
“…There was also no significant difference overall in cancer deaths between the groups assigned to more intensive vs less intensive glucose lowering. The overall cancer event rate observed in our study of patients with long standing type 2 diabetes (1.33 per 100 PY) was similar to that of one large population-based study of people with diabetes (1.31 per 100 PY) [23] and [24]. Notably, both these cohort studies also examined cancer incidence in individuals free of diabetes and reported lower overall event rates (1.19 and 0.77 per 100 PY, respectively).…”
Section: Discussionsupporting
confidence: 87%
“…Reduced risk was found for skin cancer (0.38, 95% CI 0.22-0.66). Among men, there was no overall increase in cancer risk observed, but a decrease of 47% in the risk of prostate cancer was found (Chodick et al 2010).…”
Section: Relationship Of Diabetes and Cancer In Epidemiological Studiesmentioning
confidence: 85%
“…Fourteen studies reported a statistically significant increase in BC incidence in patients with diabetes mellitus (Goodman et al 1997, Sinagra et al 2002, Michels et al 2003 Troisi et al 1998, Weiss et al 1999, Baron et al 2001, Mink et al 2002, Lawlor et al 2004, Khan et al 2006, Garmendia et al 2007, Sellers et al 2007, Perrin et al 2008, Sanderson et al 2010, Lambe et al 2011, Carstensen et al 2012, Cleveland et al 2012, Yu et al 2012 while six studies favoured a decreased risk (Moseson et al 1993, Inoue et al 2006, Rollison et al 2008, La Vecchia et al 1994, Sella et al 2011, Chlebowski et al 2012. Three studies found no association between the two (Franceschi et al 1990, Chodick et al 2010, Bowker et al 2011. Quantitative analysis revealed a significant pooled risk point estimate of 1.20 (95% CI 1.13-1.29) (Fig.…”
Section: Non-specific Diabetes Mellitusmentioning
confidence: 98%